The Psychological Well-Being of Student Activists - Casmini, Casmini; Suyatno, Suyatno (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2021)
Psychological well-being has a role in determining the quality of life of student activists. This study aims to describe the meaning of psychological well-being in student activists, and their influence on the forms of behavior carried out. The research subjects were 42 people in collecting data on the profile of student activists from UIN Sunan Kalijaga Yogyakarta, and 14 students were subjects who gave information verbally and in the form of non-verbal activities related to the meaning of psychological well-being and behavior carried out as an implication of the meaning of psychological well-being. Data on the profile of student activists were explored by in-depth interviews using face-to-face interviews and what excavated key data on psychological well-being with focus group discussions (FGD). The results of this study illustrate that the essence of the psychological well-being of student activists is happiness and satisfaction in life based on trust in Allah. Expressions of happiness and life satisfaction in activist students are very diverse and have implications for academic, social, and spiritual forms of activity or behavior.